Poetry, print, and the making of postcolonial literature - Suhr-Sytsma, Nathan (Cambridge, United Kingdom Cambridge University Press, 2017)
The book reveals how mid-twentieth-century African, Caribbean, Irish, and British poets profoundly affected each other in person and in print.
Introduction: Negotiating the era of decolonization -- Provincializing the Greenwich Meridian -- Interchapter: Mbari publications and the CIA -- Editing the commonwealth -- Interchapter: Derek Walcott and the London Magazine -- Fashioning the modern African poet -- Interchapter: James Simmons's Nigeria and the honest Ulsterman -- Publishing the troubles -- Conclusion: the haunting of Seamus Heaney and Geoffrey Hill.
Includes bibliographical references and index.
Keywords: Commonwealth poetry (English) -- History and criticism; English poetry -- 20th century -- History and criticism; Postcolonialism -- Commonwealth countries; Postcolonialism in literature; Colonies in literature